Green and eco-friendly adsorption of dyes with organoclay: isothermal, kinetic and thermodynamic studies. (2nd October 2022) - Tariq, Shahzaib; Saeed, Muhammad; Zahid, Usman; Munir, Maimoona; Intisar, Azeem; Asad Riaz, Muhammad; Riaz, Aqsa; Waqas, Muhammad; Abid, Hafiz Muhammad Waqar
Abstract: The present study comprises the surfactant-based modified adsorbents as inorgano–organo composites for the removal of dyes. It was depicted that 0.05 g of modified clay could be efficiently used to adsorb >90% of dye (100 mg/L). The kinetic models (pseudo-first order, pseudo-second order, intraparticle diffusion model) and isothermal models (Langmuir, Freundlich, Temkin) were also studied to examine the adsorption mechanism. Pseudo second-order kinetic model and Langmuir isothermal model fitted well with adsorption of dyes. The thermodynamic ( Δ G °,   Δ H °   and   Δ S ° ) parameters were also studied and negative value of ( Δ G ° ) and positive value of ( Δ S ° ) indicates the spontaneity of adsorption.